Konsep Matematika dalam Budidaya dan Pengolahan Kopi Tangsi Wangi Gununghalu : Studi Etnomatematika - Rismawati, Rima; Darojat, Ayi; Aripin, Usman (Lattice Journal : Journal of Mathematics Education and Applied, 2025)
Coffee not only plays a role as an economic commodity, but also represents a social phenomenon closely related to calculation and ratio activities. The connection between farmers and mathematical concepts is known as ethnomathematics, which serves to bridge abstract mathematical concepts with the culture and real lives of students. This study aims to explore ethnomathematics comprehensively in the cultivation and processing stages of Tangsi Wangi coffee in Gununghalu Village and to provide a source of contextual mathematics learning. The research method used is a qualitative method with an ethnographic approach through observation, in-depth interviews, and documentation of the entire production process. The results of the study show that mathematical concepts are found in six stages, namely planting, harvesting, fermentation, drying, roasting, and brewing. Specifically, the concept of plane geometry is seen in the planting of 2×2 meter squares to optimize the land, while solid geometry is seen in the use of cylindrical drums during fermentation. Arithmetic sequences were identified in the routine harvesting schedule every 10 days. The concepts of comparison and ratio were applied to fertilizer measurements, the ratio of water and coffee powder during brewing, and the calculation of coffee bean weight reduction from 1 kg to 0.8 kg after roasting. Social arithmetic was found in the calculation of yield and determination of package weight. These findings show that local cultural practices are a rich source of mathematics learning and can be used as culture-based teaching materials for more contextual learning while supporting cultural preservation. Kopi tidak hanya berperan sebagai komoditas ekonomi, tetapi juga merepresentasikan fenomena sosial erat dengan aktivitas perhitungan dan rasio. Keterkaitan antara petani dan konsep matematika tersebut dikenal sebagai etnomatematika, yang berfungsi menjembatani konsep matematika abstrak dengan budaya serta kehidupan nyata siswa. penelitian ini bertujuan mengeksplorasi etnomatematika secara menyeluruh pada tahapan bududaya dan pengolahan kopi Tangsi Wangi di Desa Gununghalu serta menyediakan sumber belajar matematika kontekstual. Metode penelitian yang digunakan adalah metode kualitatif dengan pendekatan etnografi melalui observasi, wawancara mendalam dan dokumentasi seluruh proses produksi. Hasil penelitian menunjukkan bahwa konsep matematika ditemukan pada enam tahapan, yaitu penanaman, pemanenan, fermentasi, dan penjemuran, roasting serta penyeduhan. Secara konkret, konsep geometri bidang tampak pada penanaman berbentuk persegi dengan jarak meter untuk mengoptimalkan lahan, sedangkan geometri ruang terlihat pada penggunaan drum silinder saat fermentasi. Barisan aritmetika teridentifikasi pada jadwal pemanenan rutin setiap 10 hari. Konsep perbandingan dan rasio diterapkan pada takaran pupuk, rasio air dan bubuk kopi saat penyeduhan, serta perhitungan penyusutan berat biji kopi dari 1 kg menjadi 0,8 kg setelah roasting. Aritmetika sosial ditemukan pada perhitungan rendemen dan penentuan berat kemasan. Temuan ini menunjukkan bahwa praktik budaya lokal merupakan sumber belajar matematika yang kaya dan dapat dimanfaatkan sebagai bahan ajar berbasis budaya untuk pembelajaran yang lebih kontekstual sekaligus mendukung pelestarian budaya.